Konsep Tentang Bakat dan Minat Jabatan Dalam Bimbingan dan Konseling - Chandra, Mutiara Putri; N, Nurfarhanah; Ardi, Zadrian (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This article is compiled using a literature review method. Previous scientific works related to the literature review are the main sources of this research. Data collection methods include books, journal articles, internet articles, and other writings related to the subject. This study analyzes how the role of ethics and aesthetics is applied in guidance and counseling services. Understanding job talents and interests is an essential component in guidance and counseling, especially in supporting students to recognize their potential and design their future careers appropriately. Talent as a natural potential and interest as a developing psychological drive, both complement each other in the career decision-making process. The role of Guidance and Counseling teachers is very strategic in this process, through the provision of assessment services, counseling, and program development that supports the exploration of students' potential. The use of measuring instruments such as GATB, DAT, and RIASEC allows for objective recognition of talents and interests, so that guidance interventions can be tailored to the needs of each individual. In addition, internal and external factors such as the family environment, school, and parental support also have a major influence on the development of student potential.